Application of Markowitz Model for Analyzing the Performance of Cricket Teams in Indian Premier League. Issue 1 (January 2015) - Singh, Ranjit; Saikia, Hemanta; Bhattacharjee, Dibyojyoti
This study tries to identify the dominant teams of the first five seasons of IPL using Markowitz model of portfolio management. An average composite performance score (ACPS) is developed based on two prime skills of the game (i.e. batting and bowling) that can be used to quantify the performance of a cricket team. The value of ACPS is considered as the return of a team and the standard deviation of the composite performance score of the team across different matches as the risk associated with team performance. The study also tries to explore if it is the dominating team that tops the list in the tournament. As an outcome of the study, it is found that Chennai Super Kings (CSK) and Delhi Daredevils (DD) had dominated the first three seasons of IPL. The next two seasons were dominated by Deccan Chargers (DC). A dominating team is expected to be the favorite team of the tournament. Such a team is expected to get more support from the audience.